ONLINE INSTRUCTION AS LOCAL EDUCATION: CUNY'S ONLINE BACCALAUREATE - Otte, George (Online Learning, 2007)
The City University of New York is taking a new, local approach to online instruction: offering an online baccalaureate for degree completers, designed for NYC students who have “stopped out” in good academic standing and need the “any time” flexibility of asynchronous learning to finish the degree. What is especially distinctive about this online program is its goal of access for local students, its core constituency and mission. Though CUNY is addressing a local problem, online access to higher education for local students may address nation-wide problems with rates of degree completion and progress towards completion. As more institutions provide online instruction, localness may well be the key to access and timely completion for local students, with time and not distance being the key obstacle it overcomes.